The Pseudolathra species of the East Palaearctic and the Oriental regions (Coleoptera: Staphylinidae: Paederinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2012)
The available types and additional material of the species of the lathrobiine genus Pseudolathra Casey, 1905 of the East Palaearctic (including Middle Asia) and the Oriental regions are revised. In all, thirteen valid species are recognised, six of which are new to science: P. brevincisa sp. n. (Thailand), P. cordiformis sp. n. (SE-India), P. himalayana sp. n. (Pakistan, N-India, Nepal), P. sagittata sp. n. (Thailand), P. transversicollis sp. n. (Thailand, N-India), and P. vellicans sp. n. (N-India). All the species of the study region are (re-)described or diagnosed; thirteen species are illustrated. Pseudolathra pulchella (Kraatz, 1859), previously a synonym of P. caffra (Boheman, 1848), is revalidated. Two synonymies are proposed: Pseudolathra pulchella (Kraatz, 1859) = P. caffra javana (Cameron, 1940), syn. n.; P. unicolor (Kraatz, 1859) = P. chujoi (Last, 1966), syn. n. Two species are moved from Lobrathium Mulsant & Rey, 1878 to Pseudolathra: P. nigerrima (Cameron, 1924), comb. n., and P. regularis (Sharp, 1889), comb. n. The East Palaearctic and Oriental species on the one hand and the West Palaearctic species on the other hand form separate phylogenetic lineages. The former are tentatively attributed to the subgenus Allolathra Coiffait, 1972 and the latter to the nominate subgenus. The species of the East Palaearctic and Oriental regions are assigned to three species groups. A key to species and a catalogue are provided. Additional records are reported, among them several new country records. The distributions of twelve species are mapped.KeywordsColeoptera, Staphylinidae, Paederinae, Lathrobiina, Pseudolathra, Palaearctic region, Oriental region, taxonomy, new species, new combinations, new generic assignments, new synonymies, key to species, catalogue, distributions.Nomenclatural Actscafrum [sic] javanum Cameron, 1940 (Lathrobium), syn. nov. of Pseudolathra pulchella (Kraatz, 1859)chujoi Last, 1966 (Lathrobium), syn. nov. of Pseudolathra unicolor (Kraatz, 1859)pulchellum Kraatz, 1859 (Lathrobium), revalidated now: Pseudolathra pulchella (Kraatz, 1859)seriatum Sharp, 1889 (Lathrobium), LT now: Pseudolathra lineata Herman, 2003 (replacent name)unicolor Kraatz, 1859 (Lathrobium), LT now: Pseudolathra unicolor (Kraatz, 1859)brevincisa Assing, 2012 (Pseudolathra), spec. nov.cordiformis Assing, 2012 (Pseudolathra), spec. nov.himalayana Assing, 2012 (Pseudolathra), spec. nov.nigerrima (Cameron, 1924) (Pseudolathra), comb. nov.; LT hitherto Lathrobium nigerrimum Cameron, 1924regularis (Sharp, 1889) (Pseudolathra), comb. nov.; LT hitherto Lathrobium regulare Sharp, 1889sagittata Assing, 2012 (Pseudolathra), spec. nov.transversicollis Assing, 2012 (Pseudolathra), spec. nov.vellicans Assing, 2012 (Pseudolathra), spec. nov.